CHARACTERISTICS OF PATHOMORPHOLOGICAL CHANGES IN THE LUNGS OF CHILDREN BORN WITH ESOPHAGUS ATRESION (Conferencea, 2022)
Severe preeclampsia has a negative impact on lung development in the second half of pregnancy, at 20-36 weeks. Sometimes abnormalities in the digestive, cardiovascular and other systems of the fetus also adversely affect the development of the lungs. The morphofunctional status of the lungs of infants born with esophageal atresia has been studied in medicine. The following changes were detected in the lungs during operative treatment of esophageal atresia in such infants: it can be seen that the lungs are in a state of formation, but the main component is a large accumulation of inflammatory cell infiltrates, consisting of lymphocytes . The lungs of infants who underwent operative treatment for esophageal atresia, stillbirths with esophageal anomalies, and newborns who died alive but aspirator pneumonia were comparable. morphological examination revealed that each case had its own unique features and symptoms. Respiratory diseases are the most common group of pathologies in childhood. Lung disease accounts for one in six deaths worldwide (1,5,10). At present, the problem of prevention and treatment of bronchopulmonary diseases in children, especially infants, remains topical. Following the normal development of the lungs in the fetus, their pathological formation is influenced by the following factors: acute polyhydramnios, diabetes mellitus, hyperthyroidism, and foci of chronic infection (2,5,7). Severe form of preeclampsia has a negative impact on lung development in the second half of pregnancy, at 20-36 weeks. Sometimes abnormalities of the fetal digestive, cardiovascular and other systems also adversely affect the development of the lungs (4,6,7). One of the important factors contributing to alveolar epithelial damage and the development of hyaline membrane disease (HMD) in preterm infants is intranatal hypoxia and amniotic fluid aspiration (2,3,6,8,9). Esophageal atresia and developmental disorders of the digestive system also directly affect the development of organs of the respiratory system. The aim of our study was to provide little information in the literature on morphofunctional changes in the lungs of newborns with esophageal atresia